A revised interpretation of the Chon Aike magmatic province: Active margin origin and implications for the opening of the Weddell Sea - Bastias Silva, Miguel Joaquin; Spikings, Richard Alan; Riley, Teal; Ulianov, Alexey; Grunow, Anne; Chiaradia, Massimo; Hervé, Francisco (Lithos, 2021)
Late Triassic – Jurassic igneous rocks of the Antarctic Peninsula and Patagonia provide evidence for the evolution of the margin of southwestern Gondwana. We present new geochronological (LA-ICP-MS zircon U\Pb dates) analyses of 12 intrusive and volcanic rocks, which are complemented by geochemical and zircon isotopic (Hf) as well as whole rock isotopic (Nd, Sr) data. These are combined with similar analyses of 73 other igneous rocks by previous studies, to constrain the magmatic evolution and Late Triassic – Jurassic tectonic setting. The distribution of crystallisation ages reveals four main magmatic pulses that collectively span ~225–145 Ma, all of which have compositions that are consistentwith a continental arc setting. The first episode occurred between ~223–200Ma, and records active margin magmatismwithin the Antarctic Peninsula and northern Patagonia, and reveals the presence of a flat-slab that gave rise to magmatism in eastern Patagonia. After a period of magmatic quiescence (~200–188 Ma), the second episode occurred between ~188 and 178 Ma, with a continuation of arc magmatismabove a flattened slab. The third episode spanned ~173–160Ma, and its geographic distribution suggests the slab was steepening, driving magmatism towards the south and west in Patagonia. Finally, the fourth period occurred between ~157 and ~ 145 Ma, during which time magmas were emplaced along the Antarctic Peninsula and western Patagonia, with no evidence for flat-slab subduction. The analysed rocks include the Chon Aike magmatic province, which has been considered to have been influenced by the break-up of Gondwana, via heating associatedwith the Karoo plume in southern Africa and the activemargin in western Patagonia and the Antarctic Peninsula. Our newdata and revised compilation nowsuggest that the Early -Middle Chon Aike Jurassic silicic magmatic province in Patagonia and the Antarctic Peninsula can be entirely accounted by active margin processes. We also show that the final stage of Jurassic magmatism (~157–145 Ma) was ...